2018
DOI: 10.1161/strokeaha.117.019261
|View full text |Cite
|
Sign up to set email alerts
|

Successful Reperfusion With Intravenous Thrombolysis Preceding Mechanical Thrombectomy in Large-Vessel Occlusions

Abstract: Pretreatment with systemic thrombolysis in patients with large-vessel occlusion eligible for mechanical thrombectomy results in SR in 1 of 10 cases, negating the need for additional endovascular reperfusion. Tandem occlusions seem to be the least responsive to IVT pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
112
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 13 publications
4
112
2
Order By: Relevance
“…8,9 Important data about the prevalence of preinterventional reperfusion was extracted from the latest large randomized trials, as shown in a recently published metaanalysis, 11 suggesting the prevalence of preinterventional reperfusion to be ≈11%. Because of the heterogeneity of reported prevalences and insufficiently detailed reperfusion quality grading, 13,20 subgroup analyses and a systematic comparison with patients not having received tPA were not performed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,9 Important data about the prevalence of preinterventional reperfusion was extracted from the latest large randomized trials, as shown in a recently published metaanalysis, 11 suggesting the prevalence of preinterventional reperfusion to be ≈11%. Because of the heterogeneity of reported prevalences and insufficiently detailed reperfusion quality grading, 13,20 subgroup analyses and a systematic comparison with patients not having received tPA were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers increased to 13 (95% CI, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 35 (95% CI, 18-464) when analysis was confined to M1 (proximal and distal) and ICA occlusions (SWIFT DIRECT trial cohort [Solitaire With the Intention for Thrombectomy Plus Intravenous t-PA Versus DIRECT Solitaire Stent-Retriever Thrombectomy in Acute Anterior Circulation Stroke], URL: http://www.clinicaltrials. gov.…”
Section: Number Needed To Treatmentioning
confidence: 99%
See 3 more Smart Citations